2022
DOI: 10.1080/12460125.2022.2062848
|View full text |Cite
|
Sign up to set email alerts
|

The role of management in fostering analytics: the shift from intuition to analytics-based decision-making

Abstract: Numerous studies have shown that approaches of AI&A decision-making have the power to increase the quality of decisions. However, many firms have not adopted these approaches and many decisions are still made intuitively. Those decisions often fail to achieve their intended results, lead to negative consequences, and sometimes must be reversed. This paper sheds light on the question of how management can drive the shift from intuitive to data-based decision-making.An in-depth single-site case study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…From literature, we know that a particular mentality could be perceived in digitalized organizations (Colli et al 2019 ), but from interviews and the structural model, we captured how much this can be related to DT (0.321, p < 0.001) and an innovative structure (0.188, p < 0.05). Improving the understanding of what a ‘digital culture looks like’ (Kane et al 2016), we echo Korherr et al ( 2022 ) and Levy et al ( 2022 ), arguing that a company that transforms is one that, among several things, has a culture that transited to data collection, analysis, and evidence-based decision making, despite making decisions based on intuition (about what customers want and or which technology is best)—a widespread behavior in SMEs. Besides resonating with the results of previous works as Fregnan et al ( 2022 ) and Roblek et al ( 2021 ), it is an organization connected to what is happening, and that cultivates critical thinking about technology, knowing how to choose and use the most appropriate technology that may improve its value proposition.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…From literature, we know that a particular mentality could be perceived in digitalized organizations (Colli et al 2019 ), but from interviews and the structural model, we captured how much this can be related to DT (0.321, p < 0.001) and an innovative structure (0.188, p < 0.05). Improving the understanding of what a ‘digital culture looks like’ (Kane et al 2016), we echo Korherr et al ( 2022 ) and Levy et al ( 2022 ), arguing that a company that transforms is one that, among several things, has a culture that transited to data collection, analysis, and evidence-based decision making, despite making decisions based on intuition (about what customers want and or which technology is best)—a widespread behavior in SMEs. Besides resonating with the results of previous works as Fregnan et al ( 2022 ) and Roblek et al ( 2021 ), it is an organization connected to what is happening, and that cultivates critical thinking about technology, knowing how to choose and use the most appropriate technology that may improve its value proposition.…”
Section: Discussionsupporting
confidence: 75%
“…Also, it is associated with the development and support of a mentality towards being capable of responding to the disruptions related to using digital technologies (Porfírio et al 2021 ; Sousa and Rocha 2019 ) and a fundamental role in triggering disruptive technology absorptive capacity within SMEs (Scuotto et al 2022 ). Regarding it, Korherr et al ( 2022 ) identified six factors that play a critical role in fostering analytics and establishing analytics-based decision-making, such as management behavior, top management and strategy, analytics infrastructure, organization and governance, HR management and development, and culture.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By drawing on 34 in-depth interviews with managers involved in data analytics in various sectors in France, this article examines the factors that influence the way in which managers approach data analytics. Our study adds to the conversation on data analytics and decisionmaking (Korherr et al, 2022;Rialti et al, 2019) and build on earlier research that point to the pivotal influence of managers on the implementation of new technologies in their organizations (Del Giudice et al, 2018;McAfee et al, 2012;George et al, 2014;Sengupta et al, 2022). More specifically, we extend this line of research by revealing that the way in which managers approach and coordinate their organization's resources through the use of data analytics in their function and organization as a whole seems to be influenced by three interrelated factors.…”
Section: Discussionmentioning
confidence: 92%
“…However, little is known about how and why managers implement and use data analytics in their job or lack to do so. Indeed, there is a lack of insights into the various approaches managers use to deal with data analytics and on which aspects these approaches are based (Korherr et al, 2022). Thus, more insights into the factors that influence the various ways in which managers effectively adopt, use and implement data analytics is important to reap the potential benefits of data analytics for organizations.…”
Section: Resource Orchestration Theorymentioning
confidence: 99%
See 1 more Smart Citation